STRADEGIES TO MAINTAIN SMOKERS RIGHTS (Tufts Archival Research Center, 2007)
Outline of various programs and departments within the tobacco industry. Includes objectives of the Center for Indoor Air Research (CIAR) and a workplace smoking program.